Blocking inhibition of prothrombinase by tissue factor pathway inhibitor alpha: a procoagulant property of heparins. (15th June 2016) - Wood, Jeremy P.; Baumann Kreuziger, Lisa M.; Desai, Umesh R.; Mast, Alan E.
Abstract : Unfractionated heparin (UFH) has procoagulant activity in antithrombin/heparin cofactor II (HCII)‐depleted plasma. UFH prevents tissue factor pathway inhibitor alpha (TFPIα) from inhibiting the procoagulant enzyme complex, prothrombinase, providing a possible mechanism for its procoagulant activity. The procoagulant potential of UFH and various low molecular weight heparins (LMWHs) were characterized for TFPIα dependence, using thrombin generation assays performed with antithrombin/HCII‐depleted plasma. UFH, the LMWHs enoxaparin and dalteparin, and the low anticoagulant LMWH 2‐O, 3‐O desulphated heparin (ODSH) all promoted thrombin generation, but fondaparinux did not, and this activity was blocked by a TFPIα antibody. UFH, enoxaparin, and dalteparin were anticoagulant in reactions containing 1–2% normal plasma. In prothrombinase activity assays, UFH, enoxaparin, dalteparin and ODSH blocked prothrombinase inhibition by TFPIα, while again fondaparinux did not. In both the plasma and purified assays, LMWHs displayed greater procoagulant potential than UFH, even when normalized to saccharide concentration. These biochemical data reveal that UFH and LMWHs, but not fondaparinux, block prothrombinase inhibition by TFPIα, thereby producing their paradoxical procoagulant activity observed in the absence of antithrombin/HCII. The findings may help to understand the complex pathophysiology and treatment of patients that are simultaneously bleeding and clotting, such as those with disseminated intravascular coagulation.